THE USE OF GROUP INVESTIGATION TO IMPROVE STUDENTSâ ABILITY IN WRITING SKILL ON ANALYTICAL EXPOSITION TEXT - Mayasari, Rina (ENCOUNTER, 2012)
Group investigation is an organizational approach that allows a class to work actively and collaboratively in small groups and enables students to take an active role in determining their own learning goals and processes. Group investigation is interesting so that the students will feel the new atmosphere in classroom and are interested in learning writing. This study is aimed to investigate the implementation of group investigation to improve studentsâ writing organization of analytical exposition text and to what extent is the improvement of studentsâ writing organization of analytical exposition text after being taught through group investigation. This study employs a classroom action research with 11th Grade students of MA Manahijul Huda Pati in the Academic year of 2011-2012. The instrument used to collect the data was observation and test. The assessment of the test result was focused studentsâ ability in writing analytical exposition. The result shows that the implimentation of Group investigation is improvement of learning tool, motivates students in doing work or jobs. The research improve students ability in writing based on their score in doing test in every cycle. The last cycle show the significant improvement of studentsâ ability. Score from pre-cycle was 57.71, the score from the first cycle was 65.71, and score from the second was 75.